Spontaneous hip dislocations in a high school basketball player - Blunk, L. B. (Journal of Athletic Training, 2019)
Background: Due to the anatomy of the hip joint it is typically a very stable joint which means great force is required to dislocate this joint. This type of dislocation is even more uncommon in adolescents. Typically, when this type of dislocation occurs it is the result of massive trauma like that of a motor vehicle accident where the hip is ? exed, and an axial load is applied to the femur when the patient`s knees are forced into the dash. This is one reason posterior dislocations are more common. The case I am presenting is unique in that its mechanism of injury was atraumatic. Patient: This case involves a 16-yearold male basketball player with ? ve years of competitive basketball experience with two episodes of spontaneous hip dislocation. This individual had no previous injury to either the involved or contralateral hip. The initial dislocation happened in June of 2017 while participating in a game with his AAU basketball team. He was dripping the ball down the court and went to sprint and cut under some pressure and fell to the ground. The second happened with his high school basketball team during practice February of 2018 while participating in a full court layup drill. Both episodes were non contact in nature. Both times basic observation and palpation revealed a hip dislocation and EMS was activated and neurovascular status monitored. There were no attempts made to reduce his hip prior to arrival at the emergency department with either episode. Radiographs obtained at the hospital con? rmed a posterior hip dislocation with a fracture to the posterior lip of the acetabulum. The patient has reduced head neck offset with an alpha angle of 75. He has a de? cient posterior wall at baseline when compared to the contralateral side resulting in increased hip instability. Intervention or Treatment: Both reductions were closed reductions performed in the emergency department under sedation. The second dislocation was accompanied with a posterior acetabular fracture that was repaired with internal ? xation. Following surgery, the patient was kept NWB for the ? rst month then transitioned to "weight of leg weight bearing" for the second month. He resumed full weight bearing by two months post-op along with gait training and glute abductor strengthening following posterior hip precautions. The literature shows us that most hip dislocations in this age group are a result of some form of acute trauma which was not present in this case. Outcomes or Other Comparisons: Following internal ? xation of the acetabular fracture this patient underwent physical therapy for approximately eight months before being medically cleared to return to sport. Conclusions: Due to the patient`s anatomical predisposition to hip instability he does have an increased risk of recurrent dislocations in the future. Risks have been explained to the patient and his family and they have elected to let him continue to play basketball without and further surgical intervention to stabilize the joint. In the event that he has another dislocation episode, a partial replacement will be considered. Clinical Bottom Line: Hip dislocations can be atraumatic, and it is important to recognize these injuries and refer immediately taking care to monitor any neurovascular changes.